2021
DOI: 10.1017/s0022377820001592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic perturbations and radiation on the runaway avalanche

Abstract: The electron runaway phenomenon in plasmas depends sensitively on the momentum- space dynamics. However, efficient simulation of the global evolution of systems involving runaway electrons typically requires a reduced fluid description. This is needed, for example, in the design of essential runaway mitigation methods for tokamaks. In this paper, we present a method to include the effect of momentum-dependent spatial transport in the runaway avalanche growth rate. We quantify the reduction of the growth rate i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…The evolution of the magnetic field through the current quench might also be of interest, potentially including deliberately induced perturbations to increase the runaway losses. Even the comparatively smaller magnetic perturbations that may be present during the current quench can have a relatively large impact on the runaway generation and dissipation [33].…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of the magnetic field through the current quench might also be of interest, potentially including deliberately induced perturbations to increase the runaway losses. Even the comparatively smaller magnetic perturbations that may be present during the current quench can have a relatively large impact on the runaway generation and dissipation [33].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of transport losses is expected to be higher in a smaller machine, which might explain why the prediction of an experimentally excluded re-heating was less common for JET than for AUG. Time dependent radial profiles of the magnetic field fluctuations are difficult to obtain from experiment, although their amplitude during the current quench has often been found to be fairly small [43]. Numerical modelling of the transport due to magnetic fluctuations [44] would therefore require exploration of a fairly large additional parameter space and the effect of this on the results presented remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…The time evolution of the modes and their saturation amplitude is a critical question to determine their potency for runaway transport. Earlier studies showed that a magnetic perturbation with an amplitude of about δB/B ≈ 0.1% is sufficient to suppress runaway avalanche [71,72], while more recent research [73] decreases this threshold by about a factor of 2.…”
Section: Interaction Of Alpha Particles and Alfvén Wavesmentioning
confidence: 98%